Financial Support System towards Micro, Small and Medium Enterprises - Gupta, Shailesh; Mathur, Anurag (Journal of Commerce and Trade, 2015)
Micro, small and medium enterprises (MSMEs) play a important role in the industrial development of the country. These enterprises contribute to the country’s GDP and are a major part of country’s industrial production, exports, etc. These firms help in generating employment across the country and also restrict concentration of wealth in few hands . These enterprises construct an entrepreneurial substratum in the economy by developing and nurturing the talents, skills, etc. and helps out in the reduction of poverty. Due to high labour intensity, this sector has been provided a priority status by both the Central and the State Governments. The MSME sector in India is heterogeneous in nature, widely dispersed and mostly unorganised. It includes various types of production units ranging from khadi, coir & crafts to technologically viable industries. The MSME’s faced various challenges related to finance, operations, marketing, infrastructural, technological and legal. Various measures are taken by Government for the upliftment of MSME’s. Traditionally private funds from family & friends are single and largest source of finance but for the exploitation of MSME’s full potential there is a requirement of private equity. Support of entrepreneurs and Government is highly required for the development of Indian Economy. For this purpose Government has launched several supportive schemes such as Credit Guarantee Fund Trust for Micro and Small Enterprises (CGTMSE), Credit Linked Capital Subsidy Scheme (CLCSS), Under Single Window Scheme financial requirements of MSME’s can be satisfied through single agency.